Development of magnetorheological brake with two coils placed on each side of the brake housing - Hung, Nguyen Quoc; Diep, Nguyen Ngoc; Dzung, Nguyen Si (Vietnam Journal of Mechanics, 2015)
In this study a new configuration of magneto-rheological brake (MRB) with  two coils placed on each side of the brake housing is proposed, optimally  designed and evaluated. With this configuration, the MRB is expected to  provide higher braking torque, more compact size than traditional MRB. After  describing an introduction of the proposed configuration, braking torque of  the proposed MRB is analyzed based on Bingham-plastic rheological model of  magnetorheological fluid (MRF). The optimization of the proposed MRB, the  MRB with one coil placed on each side of the brake housing and the  conventional MRB is then performed considering maximum braking torque and  mass of the brakes Based on the optimal results, advanced performance  characteristics of the proposed MRB are figured out.